Urinary tract infection in men with AIDS. Issue 1 (February 1994) - De Pinho, A M; Lopes, G S; Ramos-Filho, C F; Santos, O da R; De Oliveira, M P; Halpern, M; Gouvea, C A; Schechter, M
Abstract : OBJECTIVE--To investigate whether bacteriuria and, specifically, symptomatic urinary tract infection (UTI) occur with increased frequency in men with HIV infection. METHODS--In this cross-sectional study we investigated three groups of men, aged from 18 to 50 years. Group A was composed of patients with a diagnosis of AIDS; Group B, of patients without HIV infection, and group C of patients with asymptomatic HIV infection. Patients with any known predisposing factor for UTI were excluded from the study. A clean-catch midstream urine sample was collected from each patient on the first day of hospital admission (groups A and B) or during a visit to the outpatient clinic (group C). Bacteriuria was diagnosed when > or = 100, 000 colony forming units/ml, urine were grown. RESULTS--There were 415 patients, 151 in group A, 170 in group B and 94 in group C. Bacteriuria was significantly more frequently in group A (20 cases, 13.3%) than in groups B (3 cases, 1.8%, p = 0.00007) and C (3 cases, 3.2%, p = 0.009). Ten cases of bacteriuria in group A (6.6%) were symptomatic while no case of symptomatic UTI was seen in groups B (p = 0.0004) and C (p = 0.008). The frequency of UTI in homosexual men with AIDS (7 cases, 6.7%) was not significantly different from that observed in men with AIDS who denied homosexuality (3 cases, 6.5%). E coli was the predominant pathogen associated with UTI. Although adequate response to a two-week course of antibiotics was observed in most cases, an in-hospital mortality rate of 20% was found among AIDS patients with symptomatic UTI. CONCLUSIONS--In the present study, the frequency of bacteriuria and symptomatic UTI was found to be increased in men with AIDS. E coli was the predominant pathogen in these cases. These data suggest that symptomatic UTI may represent a relevant cause of morbidity for men with AIDS.